Design and implementation of a low cost optical based paint viscosity control device - Pham, Thi Thu Hien; Phan, Quoc Hung; Nguyen, Duy Anh; Le, Ngoc Bich (Vietnam Journal of Science and Technology, 2022)
In this study, a full-scale prototype of a water-based printer’s paint viscosity control device was proposed and conducted. Specifically, a novel approach of low-cost paint viscosity determination by exploiting the optical sensing method was proposed and a full-scale prototype was developed to exhibit the proposed concept. The feasibility of the proposed device was demonstrated by measuring the accuracy, setpoint control deviation and estimating its development cost. An accuracy of 1.5 cSt and a standard deviation of 1 cSt were recorded by comparing the measured viscosity data with the Zahn cup measuring method. The viscosity control results at a setpoint value of 40 cSt gave a variation of 0.8 cSt. The convergence time from initial 45 cSt to 40 cSt viscosity was 10 minutes. The developed cost was excessively competitive and was only one-fifth of the comparable commercial products. Furthermore, the device had solid and lightweight features, making it straightforward for portable applications.